PERLINDUNGAN HUKUM BLOGGER BERITIKAD BAIK TERHADAP DOMINE NAME MEREK TERKENAL DARI DUGAAN PEMBONCENGAN REPUTASI (PASSING OFF) - DESY KUSUMA WARDHANI (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
This Research entitled "Legal Protection Against Blogger Good Faith Domine Name Of Alleged Deception Famous Brand Reputation (Passing Off)". The problem of this study was, first: How does the domain name in a legal setting in Indonesia. Second: What is the legal protection of domain name for blogger’s good faith if there are similarities with the domain name famous brand. This research method using normative methods, the legal research done by examining library materials. Which refers to the legal norms contained in the legislation, international conventions, international agreements and court decisions. The results showed, first: The domain name has been linked closely with the brand and copyright but the domain name is not synonymous with the brand and copyright, as it has a system and registration requirements as well as the recognition of the existence differently. So far there are kekososngan norms that specifically regulate the domain name issue in Indonesia. Until now, the settings used by the international ICANN (Internet Corporation for Assigned Names and Numbers), the competent authority dealing with internet IP Addres, and domain name system management. Second: Legal protection for bloggers acting in good faith if there are similarities regarding the domain name can be a famous brand is preventive legal protection and the protection of repressive laws which refers to the settlement of a litigation matter (referring to the legal protection of IPR, Civil, Criminal and Law ITE) and non-litigation (both ADR and UDRP).